A case of paraproteinaemia with systemic amyloidosis: a progression or merely a coincidence? / Izzatul Aliaa Badaruddin ... [et al.] - Badaruddin, Izzatul Aliaa; Nasuruddin, Dian Nasriana; Ithnin, Azlin; Yusof, Nurasyikin; Md Mansor, Munirah (Faculty of Medicine, 2023)
Paraprotein is commonly associated with plasma cell myeloma. However, certain diseases may also be associated with paraprotein. We present an unusual case of a 55-year-old woman with systemic amyloidosis and concomitant monoclonal gammopathy of undetermined significance (MGUS). The patient presented with symptoms of acute onset of cardiac failure with discordant findings between echocardiogram and magnetic resonance imaging of the heart, suggesting infiltrative cardiomyopathy and hypertrophic cardiomyopathy. She was otherwise free of any myeloma-defining events. Radio-imaging showed a constellation of findings suggestive of systemic amyloidosis. The presence of paraprotein was not pathognomonic of plasma cell myeloma. A low concentration of paraprotein may be associated with systemic amyloidosis.